The truth about Twinkie Pie - Yeh, Kat (Little, Brown and Company, 2017)
Twelve-year-old GiGi and her junior-high-dropout sister DiDi have just won a million dollars in prize money, meaning they can move from their trailer park in South Carolina up to the North Shore of Long Island, where along with a better life they also uncover secrets about their family's past.